Relationship between the Family of Origin Health and Marital Satisfaction among Women in Bentolhoda Hospital of Bojnurd: A Study in the North East of Iran - Sima Sadat Hejazi; Fatemeh Jalal Marvi; Shima Nikbakht; Arash Akaberi; Azadeh Kamali; Mohammad Ghaderi (Zanjan University of Medical Sciences and Health Services, 2021)
Background: Many factors affect marital satisfaction as one of the determinants of mental health, and may even lead to marital dissatisfaction. Objectives: This study aimed to determine the relationship between the health of the family of origin and marital satisfaction and its components among women in Bojnurd, Khorasan, Iran. Methods: In this descriptive correlational study, 218 women who met the inclusion criteria referred to Bentolhoda Hospital in Bojnurd as inpatients or outpatients. They were selected using the convenience sampling method from January to April 2015. The data collection tools were the Family of Origin Health Scale (FOS) and Marital Satisfaction Index (MSI). Data analysis was performed using chi-square, t-test, Pearson correlation coefficient, and multiple linear regression at p=0.05 with SPSS software version 16. Results: The study participants' mean age and duration of marriage were 31.40±8.90 and 11.10±9.30 years, respectively. The coefficient of correlation between FOS (136.52±26.93) and MSI (58.73±34.20) was negative, and their relationship was statistically significant (r=-0.365, p<0.001). There was a statistically significant difference between the mean scores of MSI for individuals who had no familiarity and the family's income before the marriage (p<0.001, p<0.007), respectively. Conclusion: Given the undesirable level of marital satisfaction and the existence of problems in family relationships as one of the factors affecting FOS and MSI in this study, as well as the multifactorial nature of marital satisfaction, further multifactorial studies are recommended to determine the factors influencing marital satisfaction to improve this variable.